“A renewal of the fraternal relations that shared blood and history demand”: Latin American Painting, Spanish Exhibitions, and Public Display at the 1910 Independence Celebrations in Argentina, Chile, and Mexico - Boone, M. (RACAR : Revue d'art canadienne / Canadian Art Review)

(untitled) (UAAC-AAUC (University Art Association of Canada | Association d'art des universités du Canada), 2013)
Centenary celebrations inspire both organizers and their guests to reflect upon the characteristics of national culture and its relationship to other cultural traditions. Exhibitions of Spanish art mounted in 1910 in three Latin American cities celebrating one hundred years of independence—Buenos Aires, Mexico City, and Santiago de Chile—offered these historically and culturally distinct places an opportunity to reflect upon their histories and current relationships with Spain. This paper uses printed news accounts and popular imagery, diplomatic correspondence, as well as artwork from Argentina, Chile and Mexico to explore a range of questions about Latin America. What do these exhibitions tell us about Spanish and Latin American art produced at this time? What do they tell us about Argentina, Mexico, Chile and their relations with Spain? And in what ways might the reception of Spanish art in these three Latin American countries help us to understand the political and cultural issues of each nation? By looking at Spain’s participation in the Latin American centenaries, issues of concern to Spain and the Americas, the creation of Latin American national identities in relationship to Europe and to each other, and the existence of a market for art in Latin America (or lack thereof) all come into play.